Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
This JIFAM volume 7 (Special Issue 2) January 2025 publishes papers related to maintenance of geotechnical infrastructure assets and problematic soil improvement methods to develop the sustainable asset management for infrastructures. As regulated in Indonesian Scientific Journal Accreditation, a Scientific Journal can publish the Regular, Supplement and Special Edition. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the seventh volume (Special Issue 2).